Ergo-Biopsychosocial Approach to Support the Quality of Life of Small Housing Inhabitants - Hartono, Markus; Tjahjoanggoro, Antonius Johanes; Tondok, Marselius Sampe; Hapsari, Indri (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2020)
A study on the intervention of human factors engineering (known as ergonomics) on sustainable living based on biopsychological needs was conducted, taking samples of small housing inhabitants. In total, 90 participants were involved. Those who were living in small housings have a significant challenge of how to live comfortably given very limited space. The measurement of the quality of human life through WHOQOL-BREF (World Health Organization Quality of Life-BREF) and ergonomics-based usability were used to describe the current human well-being satisfaction, to propose the modified physical facilities, and to validate the proposed design and improvement. The findings showed that all implemented improvements have supported the inhabitant’s quality of life.